Predictors of adherence and persistence to disease-modifying therapies in Multiple Sclerosis. (October 2021) - Zanga, Gisela; Drzewiscki, Estefania; Tagliani, Paula; Smietniansky, Maximiliano; Esnaola y Rojas, Maria M.; Caruso, Diego
Background and Aims: In multiple sclerosis (MS), non-adherence/non-persistence is related to suboptimal response to treatment, including disease relapses and the need for more expensive healthcare. The aim of this study was to identify predictors related to adherence to disease modifying therapies (DMTs) in a cohort of Argentinian MS patients. Methods: We conducted a cross-sectional study at the National Medical Care Program from Argentina. MS patients with at least one claim for a DMT from 1 January 2017 to 1 October 2017 were identified. A telephone survey was performed to assess clinical and demographic factors. The medication possession ratio (MPR) was used to estimate adherence; MPR <80% defined non-adherence. Associations were studied using a logistic regression model. Results: Our database included 648 MS patients. A total of 360 patients (60% females, mean age 55.3 years) accepted to participate. Of these, 308 (85.5%) patients were receiving DMT at the time of the survey. Some 198 (63.7%) were receiving injectable therapies. Optimal adherence was 47.7%. Adherence was associated with oral medication [odds ratio (OR) 1.83 95% confidence interval (CI) 1.13–3.00, p  = 0.014]. A factor related to oral drugs was higher educational level (OR 2.86 95%CI 1.41–5.81, p  = 0.004). Conclusion: This real-world study showed better adherence and persistence on treatment with oral therapies in MS patients in Argentina.